Comparison of the antimicrobial activity of Manuka honey and native honey against methicillin resistant staphylococci from asymptomatic healthcare workers. - SK. Jasmine Shahina; Padma Krishnan (International Journal of Phytomedicine, 2013)
Asymptomatically colonized healthcare workers are the major source of Methicillin-Resistant Staphylococcus aureus (MRSA) in the hospital environment and serve as links in the transmission of MRSA among patients. Honey is known for antimicrobial properties due to various factors including phytochemical components eg: methyl glyoxal (MGO). Hence, the present study was designed to compare the antimicrobial activity of Manuka honey with native honey against methicillin resistant staphylococci from asymptomatic health care workers. Nasal swabs were collected from anterior nares of 100 healthcare workers from the hospital set up and a total of 36 isolates of staphylococci (36%) were obtained. The study has shown 7% carriage rate of MRSA and 9% MRCoNS among the healthcare workers. Initial screening with agar well diffusion method with Manuka honey showed higher inhibitory activity against all the methicillin resistant staphylococcal isolates giving a zone size of ≥ 30 mm at 50%( v/v) compared to native honey which gave zone size of 12 mm for 50% (v/v). Lower MIC of methicillin resistant staphylococci was seen for Manuka honey (6.3% to 12.5%), while the MIC of the native honey was found to be 50% in our study. The present study shows higher efficacy of Manuka honey compared to native honey against both MRSA and MRCoNS. Manuka honey shows promise as an antibacterial agent for methicillin resistant staphylococcus.